Tumor-specific PET tracer imaging and contrast-enhanced Mri based tumor volume differences inspection of glioblastoma patients - Irshad Ahmed Abbasi; Mohammed Alshehri; Yahya AlQahtani (Scientific Reports)
Abstract Despite advancements in treatment strategies, glioblastoma, also known as GBM, remains an exceptionally aggressive primary brain tumor with a grim prognosis. Despite innovations in treatment strategies, GBM continues to pose significant challenges. The assessment of GBM mainly depends on neuroimaging methods, with contrast-enhanced magnetic resonance imaging (MRI) being the widely accepted standard. In recent years, positron emission tomography (PET) has emerged as a supplementary imaging modality offering insights into the biological behavior and aggressiveness of GBM tumors. PET, often referred to as PET, complements MRI in the diagnostic process of GBM. The objective of this study was to explore the potential advantages of combining PET and MRI in diagnosing GBM. Twenty-two patients diagnosed with GBM underwent four 18 F-fluorothymidine (FLT)-PET/MRI examinations before and during treatment. Advanced image analysis methods, including MATLAB and the imlook4d analysis platform, were employed. These methods encompassed adaptive threshold algorithms, batch processing pipelines, and image attribute extraction algorithms. MRI evaluations revealed significant variations in tumor response to radiation therapy among patients with long-term and short-term survival rates, as determined by the study findings (p < 0.04). Furthermore, PET measurements, including maximum standardized uptake value (SUVmax), PET tumor volume, and total lesion activity (TLA), showed trends toward statistical significance; however, the differences did not reach conventional significance thresholds. These results underscore the need for further research into the therapeutic efficacy of PET parameters in managing this aggressive brain tumor. The findings of this study highlight the potential of fusion imaging using PET and MRI as an effective diagnostic technique for glioblastoma multiforme (GBM) and emphasize the importance of ongoing research in this area to improve patient outcomes.